Circular RNA expression profiles in synovial fluid: a promising new class of diagnostic biomarkers for osteoarthritis - Yu, Fangyuan; Xie, Congqin; Sun, Jitong; Feng, Huicheng; Huang, Xunwu (International journal of clinical and experimental pathology, 2018)
Previous studies suggest that circRNAs abnormally function in the progression of osteoarthritis (OA). However, little is known about the diagnostic value of circRNAs in patients with OA. To assess potential applications of circRNAs as diagnostic tools in OA, expression profiles of circRNAs in synovial fluid from OA patients and healthy subjects were obtained. Microarray analysis was performed to profile the expression of circRNAs in an unbiased manner. CircRNA expression in synovial fluid was identified by real-time quantitative polymerase chain reaction (RT-qPCR). The diagnostic value was evaluated using receiver operating characteristics (ROC) curves and the area under the ROC curves (AUC). Spearman correlation analysis was performed to assess the correlation of circRNAs and clinical parameters. We identified five circRNAs that were significantly elevated in synovial fluid from OA patients compared with those of the healthy controls. Among these five circRNAs, hsa_circ_0104873, hsa_circ_0104595, and hsa_circ_0101251 could effectively separate patients with OA from healthy controls with high AUC (0.683, 0.708 and 0.754, respectively). Furthermore, we found that three circRNAs were positively correlated with the degree of radiographic grading and symptomatic severity of OA patients. This study suggests that increased expression of hsa_circ_0104873, hsa_circ_0104595, and hsa_circ_0101251 in synovial fluid from OA patients may serve as potential biomarkers for OA screening.